PENGARUH SELF COMPASSION DENGAN BODY DISSATISFACTION PADA MAHASISWA ABI FISB IWU - LUSIANA, VINA; SAPUTRA, BANYU (HEALTHY : Jurnal Inovasi Riset Ilmu Kesehatan, 2024)
Body Dissatisfaction problems are caused by wrong views and self-judgments. This assessment usually takes the form of a view that the individual has experienced weight gain which causes their body to deviate from the image of the "ideal body shape". So many teenagers like to compare themselves with other people, the ability of Self Compassion can reduce comparing behavior which can lead to dissatisfaction with body shape. Researchers are interested in knowing the relationship between Self Compassion because it is considered as one of the factors that can reduce Body Dissatisfaction seen from the demands of its developmental tasks. The initial hypothesis was that the higher the sense of Self Compassion, the smaller the sense of Body Dissatisfaction. Vice versa. If the sense of Self Compassion is smaller. then the feeling of Body Dissatisfaction will be greater. The research that will be applied to answer the hypothesis is quantitative research which aims to analyze the relationship between Self Compassion and Body Dissatisfaction. In this study, correlation was used to see the relationship between the variables Self Compassion and Body Dissatisfaction. To analyze questionnaire data, several steps are carried out, namely: Validity, Reliability and Normality Tests. Tests using linear regression analysis show that Self Compassion is able to significantly predict the Body Dissatisfaction variable. If we look at the results of the correlation test, the correlation between the variables Self Compassion and Body Dissatisfaction shows a figure of 0.83. This figure shows a perfect correlation. Based on the results of the regression test, the R Square value was obtained which explains the ability of the Self Compassion (X) variable in predicting the value of the Body Dissatisfaction (Y) variable of 0.0332 or 3.3% indicating the contribution made by Self Compassion with Body Dissatisfaction). For the F test, the significance value is 0.91 > 0.05, so it is accepted and H0 is rejected. The decision is that the probability number from the calculation results is 0.270, the probability number is 0.270 > 0.05, then H1 is accepted and H0 is rejected. So based on the results of the hypothesis analysis, it was found that there was no significant influence between the Self Compassion variable and a decrease in Body Dissatisfaction (Y) in ABI FISB IWU students. ABSTRAKPermasalahan Body Dissatisfaction disebabkan oleh pandangan serta penilaian diri yang keliru. Penilaian tersebut biasanya berupa pandangan bahwa individu telah mengalami kenaikan berat badan yang menjadikan tubuhnya menyimpang dari gambaran “bentuk tubuh ideal”. Sehingga banyak remaja yang suka membandingkan dirinya dengan orang lain, adanya kemampuan Self Compassion yang mampu mengurangi perilaku membanding-bandingkan yang dapat mengarah pada munculnya ketidakpuasan bentuk tubuh. Peneliti tertarik mengetahui hubungan antara Self Compassion karena dianggap sebagai salah satu faktor yang dapat mengurangi Body Dissatisfaction dilihat dari tuntutan tugas perkembangannya. Hipotesis awal dianggap semakin tinggi rasa Self Compassion, maka rasa Body Dissatisfaction akan semakin kecil. Begitu pula sebaliknya. Apabila rasa Self Compassion lebih kecil. maka rasa Body Dissatisfaction akan semakin besar. Penelitian yang akan diterapkan untuk menjawab hipotesis adalah penelitian kuantitatif yang bertujuan untuk menganalisis hubungan antara Self Compassion dengan Body Dissatisfaction. Pada penelitian ini korelasi digunakan untuk melihat adanya hubungan antara variabel Self Compassion dengan Body Dissatisfaction. Untuk analisa data angket maka dilakukan beberapa langkah yaitu: Uji Validitas, Reabilitas dan uji normalitas. Pengujian menggunakan analisis regresi linear menunjukkan bahwa Self Compassion mampu memprediksi secara signifikan variabel Body Dissatisfaction. Jika dilihat dari hasil uji korelasi, maka korelasi antara variabel Self Compassion dengan Body Dissatisfaction menunjukkan angka sebesar 0,83. Angka ini menunjukkan adanya korelasi yang sempurna. Berdasarkan hasil uji regresi diperoleh nilai R Square yang menjelaskan kemampuan variabel Self Compassion (X) dalam memprediksi nilai variabel Body Dissatisfaction (Y) sebesar 0,0332 atau 3,3% menunjukkan kontribusi yang disumbangkan Self Compassion dengan Body Dissatisfaction). Untuk Uji F nilai signifikansi 0,91 > 0,05 maka diterima dan H0 ditolak. Keputusannya yaitu angka probabilitas dari hasil perhitungan adalah sebesar 0,270, angka probabilitas 0,270 > 0,05, maka H1 diterima dan H0 ditolak. Jadi berdasarkan hasil analisis hipotesa ditemukan bahwa tidak terdapat pengaruh yang signifikan antara variabel Self Compassion dengan penurunan Body Dissatisfaction (Y) pada mahasiswa ABI FISB IWU.